Assessment of Health-Related Quality of Life among Hypertensive Patients of Loralai, Pakistan - Khan, Mirza; Ul Haq, Noman; Riaz, Sohail; Nasim, Aqeel; Sadiq, Yasir Saud; Zarak, Muhammad Samsoor; Shahwani, Nisar Ahmed (Journal of Pharmacy Practice and Community Medicine)
Objective: This study was conducted to evaluate the health related quality of life of patients suffering from hypertension attending government hospital (DHQ) Loralai, Pakistan. Methodology: A cross-sectional descriptive study that was conducted from December 2015 to August 2016 in the Government District Hospital (DHQ) Loralai, Pakistan. Convenient sampling method was used to collect data. A self-administrative pre validated slandered questionnaire, EQ-5D, was distributed and collected after completion. The data was computed and analysed using IBM SPSS V. 22. Descriptive analysis and inferential statistics were applied. Results: Three hundred and thirty one patients participated in the study. The mean age was 47.10 (+15.29) years. Majority of patients, 55.6 % (n=184), were men. The mean (SD) of duration of high blood pressure was 2.45 (± 1.2) years. Most of the patients 54.7% (n=181) had no income. Most of the patients (46, 13.9%) showed no difficulties in the 1st, 2nd, 3rd and 4th domain whereas some problems in the 5th domain. Age group, marital status and occupation showed significant difference. Conclusion: The results of the study confirmed that Health related aspects of life are adversely altered in high blood pressure. Health-care authorities should provide adequate health facilities to the public and maintain check and balance on the delivery of health care services.
Keywords: HRQoL; Hypertension; QOL; HRQoL in high blood pressure; EQ-5D; Cross-sectional study; Loralai; Pakistan